Comparison of Conventional Systems Credit Card and Credit Card Shariah as Alternative Construction Credit Card on Banking System - Hadi, Sholikul; Hafidudhin, Didin; Tanjung, Hendri (Jurnal Manajemen, 2018)
This study was motivated by the presence of different views on whether or not allowed to use Islamic credit cards, although the Indonesian Council of Ulama (MUI) has issued a fatwa on the permissibility of the card. Given these differences, this study examines the operating system on credit cards in terms of Islamic law, a difference of conventional and Islamic Credit Card and alternative solutions Credit Card reconstruction system in accordance with the Islamic Shari'ah and can be applied in the modern economy.The results showed (1) Credit Card operating system in terms of Sharia Islamic law indicates permitted use; (2) Found some fundamental differences between Islamic and conventional Credit Card; (3) An alternative solution in the reconstruction of the Credit Card in accordance with Islamic law, including: (a) the credit card must be received recognition from banks with partnershipnya; (b) the credit card should be simple, both in the process of obtaining and using it; (c) The credit card issuer must be heavily promoting.